A method for preparing a uranium dioxide single crystal using a eutectic salt flux

CN116876071BActive Publication Date: 2026-10-30QIANWAN INST OF CNITECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310733008.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2026-10-30
Estimated Expiration
2043-06-20

AI Technical Summary

Technical Problem

由于UO2本身的熔点高至2500℃以上,因此很难通过常用的熔体法或电化学方法获得UO2晶体,更多的也只是由UO2粉末通过助熔剂高温熔解降温生长单晶,且很少有直接通过U3O8获得UO2单晶的制备

Benefits of technology

[0034]1、本发明以U3O8为原料,结合CsCl-CsF共晶盐助熔剂,惰性气氛下在Ag坩埚中反应,以“一锅式”方法制备得到单晶UO2,有效解决了熔体法无法熔解高熔点UO2的制备问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116876071B_ABST
    Figure CN116876071B_ABST
Patent Text Reader

Abstract

The application belongs to the field of nuclear fuel preparation and the technical field of crystal preparation, and relates to a method for preparing uranium dioxide single crystal by using eutectic salt fluxing agent. The method comprises the following steps: S1, loading U3O8 powder and CsCl-CsF eutectic salt into an Ag crucible; S2, then placing the Ag crucible in a ceramic crucible, and performing heat treatment in an inert atmosphere, and then performing cooling treatment to room temperature, and cleaning to obtain UO2 single crystal. The application takes U3O8 as raw material, combines with CsCl-CsF eutectic salt fluxing agent, and reacts in the Ag crucible in the inert atmosphere, so that the single crystal UO2 is prepared by the "one-pot" method, and the problem that the high-melting-point UO2 cannot be dissolved by the melt method is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of nuclear fuel preparation and crystal preparation technology, and relates to a method for preparing uranium dioxide single crystals using eutectic salt flux. Background Technology

[0002] The oxidation of UO2 has been studied for over 60 years. Today, UO2 remains an important uranium compound for nuclear fuel in commercial nuclear reactors worldwide, and it can also be used to prepare safe and durable dry storage substrates for spent fuel.

[0003] In its natural environment, UO2 possesses an ideal fluorite structure (AX2), but during heating, UO2 is extremely easily oxidized into non-stoichiometric oxides UO. 2+X The oxidative stoichiometry of UO2 can continuously increase to UO3, and different phases exist during the transformation of UO2 to UO3. Structurally, UO... 2+X (X<0.5) can be considered as fluorite-related structures. These related structures may have different symmetries, meaning that oxygen atoms are always in a disordered state in this fluorite-related lattice. As the oxygen content in the preparation environment further increases, the oxygen atoms gradually become ordered in the lattice, eventually yielding advanced uranium oxides such as U4O9, U3O7, U2O5, and U3O8. Single-crystal UO2 is beneficial for achieving directional fixation of the oxygen state, laying the foundation for accurately understanding the oxidation mechanism of uranium oxides. Furthermore, single-crystal UO2 is also significant for the subsequent targeted development of uranium oxide fuel rods and the application of high-performance uranium oxide devices.

[0004] To date, the crystal structure of UO2 can be determined by neutron diffraction experiments after high-temperature synthesis at thousands of degrees Celsius, based on thermodynamic equilibrium. In contrast, neutron diffraction results are prone to deviations from the true values ​​and exhibit significant dispersion, limiting detection precision (compared to the mature technology of SC-XRD). It is difficult to accurately calibrate unit cell parameters, and its generalizability is low, while also being more expensive. SC-XRD, however, has irreplaceable advantages over neutron diffraction in precisely determining unit cell parameters, especially since most lattice parameters in current crystal structure databases are derived from SC-XRD results. Therefore, the growth of UO2 single crystals is of great significance in meeting the sample requirements for SC-XRD.

[0005] Currently, the most common method for preparing UO2 powder is the melt method, which requires sintering temperatures of over 1000 degrees Celsius and involves a complex process. A few methods utilize electrolytic reduction or electrodeposition to obtain UO2 powder, using alkali metal halides as the electrolyte and U3O8 as the working electrode. Because UO2 itself has a melting point exceeding 2500℃, it is difficult to obtain UO2 crystals using common melt or electrochemical methods. More often, UO2 powder is melted at high temperatures with a flux and then cooled to grow single crystals; direct preparation of UO2 single crystals using U3O8 is rare. Summary of the Invention

[0006] The purpose of this invention is to address the shortcomings of existing technologies by providing a method for preparing uranium dioxide single crystals using eutectic salt flux. This method enables the growth of UO2 single crystals using U3O8 powder as raw material at temperatures below 1000°C, resulting in deep reddish-brown to black single crystals that can undergo single-crystal X-ray diffraction. This solves the problem of difficulty in preparing uranium dioxide single crystals using common melt methods, thereby accurately obtaining unit cell parameters.

[0007] One objective of this invention is achieved through the following technical solution:

[0008] A method for preparing uranium dioxide single crystals using a eutectic salt flux includes the following steps:

[0009] S1. Place U3O8 powder and CsCl-CsF eutectic salt into an Ag crucible;

[0010] S2. Then, the Ag crucible is placed in a ceramic crucible and heat-treated in an inert atmosphere, followed by cooling to room temperature and cleaning to obtain UO2 single crystals.

[0011] CsCl-CsF eutectic salt, used as a flux, has a low eutectic point. When U3O8 powder and CsCl-CsF eutectic salt are mixed and heat-treated at high temperature, the U3O8 powder begins to melt at the eutectic point of the flux CsCl-CsF (approximately 450°C), resulting in a homogeneous molten state. The fluorides in the CsCl-CsF eutectic salt corrode the Ag crucible in the reaction vessel, oxidizing Ag to Ag₂. + U3O8 is fully reduced to UO2; finally, the product of the reaction is slowly cooled to achieve supersaturation in the molten state, which drives crystal growth and yields UO2 single crystal.

[0012] In this article, inert atmosphere includes one or both of nitrogen atmosphere and argon atmosphere.

[0013] Preferably, the preparation method of the U3O8 powder includes the following steps:

[0014] S1a. One or more of uranyl tricarbonate (NH4)4[UO2(CO3)3], uranyl nitrate (UO2(NO3)2), and ammonium diuranate (NH4)2U2O7 are placed in a ceramic crucible and reacted in a muffle furnace under an air atmosphere to obtain U3O8 powder.

[0015] S1b. Detect the phase purity of the U3O8 powder prepared above. If U3O8 is not a pure phase, put the U3O8 powder into a ceramic crucible again, and react it in a muffle furnace under an air atmosphere. Repeat the above steps until the obtained U3O8 powder is a pure phase.

[0016] Further preferably, the preparation method of the U3O8 powder includes the following steps:

[0017] S1a. One or more of uranyl tricarbonate (NH4)4[UO2(CO3)3], uranyl nitrate (UO2(NO3)2), and ammonium diuranate (NH4)2U2O7 are placed in a ceramic crucible and reacted in a muffle furnace under an air atmosphere to obtain U3O8 powder.

[0018] S1b. Detect the phase purity of the U3O8 powder prepared above. If U3O8 is not a pure phase, put the U3O8 powder into a ceramic crucible again, and react it in a muffle furnace under an air atmosphere. Repeat the above steps until the obtained U3O8 powder is a pure phase.

[0019] S1c, Place the pure phase U3O8 powder into a ceramic crucible again and react it in a muffle furnace under an air atmosphere;

[0020] S1d, then repeat step S1c 0 to 3 times.

[0021] Repeated high-temperature treatment of pure-phase U3O8 powder resulted in UO2 single crystals with more complete and defect-free quality.

[0022] In the above method for preparing U3O8 powder, uranyl nitrate is preferably used as the reactant. Using uranyl nitrate as the reactant to prepare U3O8 powder is beneficial for obtaining high-quality UO2 single crystals.

[0023] In the above-mentioned method for preparing U3O8 powder, preferably, the reaction temperature in the muffle furnace is 600-800℃, more preferably 650-750℃, and the reaction time in the muffle furnace is 10-40h, more preferably 20-30h.

[0024] The ceramic crucibles mentioned in this article can be categorized as Al2O3 crucibles, quartz crucibles, zirconia crucibles, silicon carbide crucibles, etc.

[0025] Preferably, the CsCl-CsF eutectic salt is formed by mixing and grinding CsCl and CsF, wherein the molar percentage of CsF in the CsCl-CsF eutectic salt is 35-60%. More preferably, the molar percentage of CsF is 40-55%.

[0026] Preferably, the mass ratio of CsCl-CsF eutectic salt to U3O8 powder is 10-50:1, more preferably 20-30:1.

[0027] Preferably, the heat treatment temperature in step S2 is 800–950°C, more preferably 820–900°C, and the heat treatment time is 15–30 h, more preferably 20–28 h.

[0028] Preferably, the temperature is increased to the heat treatment temperature at a rate of 200–400 °C / h.

[0029] Preferably, the cooling process in step S2 includes cooling at a rate of 2–8 °C / h. This slow cooling method allows the reacted product to reach a supersaturated molten state, driving crystal growth.

[0030] Further preferably, the cooling process in step S2 includes: cooling to 300-650°C at a rate of 2-8°C / h, then stopping temperature control and allowing it to cool naturally to room temperature. Further preferably, the cooling process in step S2 includes: cooling to 300-500°C at a rate of 2-8°C / h, then stopping temperature control and allowing it to cool naturally to room temperature. Stopping the programmed temperature control at a slow cooling rate of 300-500°C, followed by natural cooling, is beneficial for preparing phase-pure UO2 single crystals.

[0031] Another objective of this invention is achieved through the following technical solution:

[0032] A UO2 single crystal, prepared by the above method, wherein the crystal size of the UO2 single crystal is (0.10~0.30)mm×(0.02~0.20)mm×(0.01~0.05)mm, and the crystal morphology is a plate-like or block-like single crystal.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. This invention uses U3O8 as raw material, combined with CsCl-CsF eutectic salt flux, and reacts in an Ag crucible under an inert atmosphere to prepare single crystal UO2 in a "one-pot" method, which effectively solves the problem that the melt method cannot melt the preparation of high melting point UO2;

[0035] 2. The CsCl-CsF eutectic salt flux used in this invention will not chemically react with UO2, nor will it form other compounds or solid solutions, which is beneficial for obtaining phase-pure UO2;

[0036] 3. The pure phase U3O8 powder of the present invention is repeatedly subjected to high temperature treatment, and the UO2 single crystal prepared from this product is more complete and defect-free.

[0037] 4. The present invention cools down at a slow rate to drive crystal growth, and the temperature control cooling is preferably set at 300-500℃, which is beneficial to the preparation of phase-pure UO2 single crystals.

[0038] 5. The UO2 single crystals prepared by this invention have an ordered arrangement of structures, which can improve the thermal conductivity of UO2 nuclear fuel to a certain extent, reduce irradiation swelling, and improve the safety of nuclear reactors.

[0039] 6. This invention provides a "one-pot" method for directly obtaining UO2 single crystals from U3O8. Compared with the commonly used melt method, the growth process is simple, the temperature is easy to control, the principle is simple and the cost is low, and it realizes the preparation of UO2 single crystals at temperatures below 1000℃. Attached Figure Description

[0040] Figure 1 The powder diffraction pattern of U3O8 prepared in Example 1 of this invention is compared with a standard card;

[0041] Figure 2 The powder diffraction pattern of the single-crystal UO2 prepared in Example 1 of this invention is compared with the standard card;

[0042] Figure 3 These are stereomicroscopic images of UO2 prepared in Examples 1-3, 5 and Comparative Example 1 of the present invention;

[0043] Figure 4 The image shows the SEM-EDS spot analysis pattern of the UO2 single crystal prepared in Example 1 of this invention.

[0044] Figure 5 The image shows a SEM image of the UO2 single crystal prepared in Example 1 of this invention and its EDS mapping analysis spectrum. Detailed Implementation

[0045] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not limit the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.

[0046] Example 1

[0047] (1) Preparation of reactant U3O8 powder

[0048] 1. Weigh 1.0g of UO2(NO3)2·6H2O and place it in an Al2O3 crucible. Under air atmosphere, place it in a muffle furnace at 700℃ and react for 24h to oxidize and generate dark green to black U3O8 powder.

[0049] 2. The powder diffraction pattern of U3O8 was obtained by powder diffraction (PXRD), and its comparison with the standard card is as follows: Figure 1 As shown, the diffraction peak positions basically conform to the standard peak values ​​and there are no impurity peaks, confirming that the U3O8 generated in the reaction is phase pure. No further high-temperature treatment is required, and it can be used for future reference.

[0050] (2) Growth of UO2 single crystals

[0051] 1. In a glove box filled with Ar gas, weigh 0.1052g of U3O8 powder obtained in step (1) and put it into an Ag crucible;

[0052] 2. Weigh 3.1g of CsCl-CsF eutectic salt (the preparation method of CsCl-CsF eutectic salt is: weigh CsCl and CsF so that the molar ratio of CsF is 45%, weigh and grind in a mortar). After thorough mixing and grinding, place the mixed eutectic salt and U3O8 powder in an Ag crucible.

[0053] 3. Cover the Ag crucible with the silver lid, and then place the Ag crucible inside the Al2O3 crucible;

[0054] 4. The mixture was heated from 25°C to 900°C at a heating rate of 300°C / h, and the reaction was maintained at 900°C for 24h.

[0055] 5. Then, the temperature was lowered to 400℃ at a rate of 3℃ / h, at which point the programmed temperature control was stopped, and the mixture was allowed to cool naturally to room temperature. After further cleaning, dark reddish-brown to black UO2 plate-like single crystals were obtained. The powder diffraction pattern of the UO2 plate-like single crystals was compared with the standard card as follows: Figure 2 As shown, the diffraction peak positions basically conform to the standard peak values ​​and there are no impurity peaks, confirming the phase purity of the UO2 generated in the reaction. Its stereomicroscopic crystal image is shown below. Figure 3-1 Further SEM-EDS point scanning was performed, such as... Figure 4 As shown, SEM imaging and EDS mapping surface scans are as follows: Figure 5 As shown, SEM imaging reveals that the crystal surface is clean, with sharp edges and a complete, defect-free crystal form. Surface scan results indicate that the crystal is mainly composed of U and O elements. Figure 5 Although the EDS structure is mainly used for qualitative analysis, it can be seen that the energy dispersive spectroscopy results of this UO2 crystal basically conform to the atomic ratio of 1:2. Figure 4 ).

[0056] Example 2

[0057] (1) Preparation of reactant U3O8 powder

[0058] 1. Weigh 1.0g of UO2(NO3)2·6H2O and place it in an Al2O3 crucible. Under air atmosphere, place it in a muffle furnace at 700℃ and react for 24h to oxidize and generate dark green to black U3O8 powder.

[0059] 2. The phase purity of the U3O8 generated by the reaction was confirmed by powder diffraction (PXRD). The diffraction peak positions basically met the standard peak values ​​and there were no impurity peaks. The U3O8 powder was placed in an Al2O3 crucible and reacted in a muffle furnace at 700℃ for 24 hours under air atmosphere. The product was then set aside for later use.

[0060] (2) Growth of UO2 single crystals

[0061] The method for growing UO2 single crystals is the same as in Example 1.

[0062] A stereomicroscope image of the UO2 sheet-like single crystal prepared in Example 2 is shown below. Figure 3-2 .

[0063] Comparing Example 1 and Example 2, it can be seen that the UO2 plate-like single crystal finally prepared by U3O8 after repeated high-temperature treatment is more complete and defect-free.

[0064] Example 3

[0065] (1) Preparation of reactant U3O8 powder

[0066] The method for preparing U3O8 powder is the same as in Example 1.

[0067] (2) Growth of UO2 single crystals

[0068] 1. In a glove box filled with Ar gas, weigh 0.1052g of U3O8 powder obtained in step (1) and put it into an Ag crucible;

[0069] 2. Weigh 3.1g of CsCl-CsF eutectic salt (where the molar ratio of CsF is 45%), mix and grind thoroughly, and then place the mixed eutectic salt and U3O8 powder in an Ag crucible;

[0070] 3. Cover the Ag crucible with the silver lid, and then place the Ag crucible inside the Al2O3 crucible;

[0071] 4. The mixture was heated from 25°C to 900°C at a heating rate of 300°C / h, and the reaction was maintained at 900°C for 24h.

[0072] 5. Then, the temperature was lowered to 550℃ at a rate of 3℃ / h, at which point the programmed temperature control was stopped, and the crystal was allowed to cool naturally to room temperature. After further cleaning, a dark reddish-brown to black UO2 blocky single crystal containing many impurities was obtained. A stereomicroscope image of the crystal is attached. Figure 3-3 .

[0073] Example 4

[0074] (1) Preparation of reactant U3O8 powder

[0075] The method for preparing U3O8 powder is the same as in Example 1.

[0076] (2) Growth of UO2 single crystals

[0077] 1. In a glove box filled with Ar gas, weigh 0.1052g of U3O8 powder obtained in step (1) and put it into an Ag crucible;

[0078] 2. Weigh 3.1g of CsCl-CsF eutectic salt (where the molar ratio of CsF is 45%), mix and grind thoroughly, and then place the mixed eutectic salt and U3O8 powder in an Ag crucible;

[0079] 3. Cover the Ag crucible with the silver lid, and then place the Ag crucible inside the Al2O3 crucible;

[0080] 4. The mixture was heated from 25°C to 900°C at a heating rate of 300°C / h, and the reaction was maintained at 900°C for 24h.

[0081] 5. Then, the temperature is reduced to 650℃ at a rate of 3℃ / h, and the temperature control program is stopped. The crystal is allowed to cool naturally to room temperature. After further cleaning, a dark reddish-brown to black UO2 blocky single crystal containing many impurities is obtained.

[0082] Comparing Examples 1, 3, and 4, it can be seen that UO2 single crystals can be prepared by reducing the temperature to 400℃, 550℃, and 650℃ using programmed temperature control. However, relatively speaking, reducing the temperature to 400℃ by programmed temperature control can better prepare phase-pure UO2 single crystals compared to 550℃ and 650℃.

[0083] Example 5

[0084] (1) Preparation of reactant U3O8 powder

[0085] The method for preparing U3O8 powder is the same as in Example 1.

[0086] (2) Growth of UO2 single crystals

[0087] 1. In a glove box filled with Ar gas, weigh 0.1052g of U3O8 powder obtained in step (1) and put it into an Ag crucible;

[0088] 2. Weigh 3.1g of CsCl-CsF eutectic salt (where the molar ratio of CsF is 50%), mix and grind thoroughly, and then place the mixed eutectic salt and U3O8 powder in an Ag crucible;

[0089] 3. Cover the Ag crucible with the silver lid, and then place the Ag crucible inside the Al2O3 crucible;

[0090] 4. The mixture was heated from 25°C to 900°C at a heating rate of 300°C / h, and the reaction was maintained at 900°C for 24h.

[0091] 5. Then, the temperature was lowered to 400℃ at a rate of 3℃ / h, at which point the programmed temperature control was stopped, and the crystals were allowed to cool naturally to room temperature. After further cleaning, dark reddish-brown to black UO2 plate-like single crystals were obtained. A stereomicroscopic image of the crystal is shown below. Figure 3-4 .

[0092] Example 6

[0093] (1) Preparation of reactant U3O8 powder

[0094] The method for preparing U3O8 powder is the same as in Example 1.

[0095] (2) Growth of UO2 single crystals

[0096] 1. In a glove box filled with Ar gas, weigh 0.1052g of U3O8 powder obtained in step (1) and put it into an Ag crucible;

[0097] 2. Weigh 3.1g of CsCl-CsF eutectic salt (where the molar ratio of CsF is 55%), mix and grind thoroughly, and then place the mixed eutectic salt and U3O8 powder in an Ag crucible;

[0098] 3. Cover the Ag crucible with the silver lid, and then place the Ag crucible inside the Al2O3 crucible;

[0099] 4. The mixture was heated from 25°C to 900°C at a heating rate of 300°C / h, and the reaction was maintained at 900°C for 24h.

[0100] 5. Then, the temperature is reduced to 400℃ at a rate of 3℃ / h, and the temperature control program is stopped. The temperature is allowed to cool naturally to room temperature. After further cleaning, a dark reddish-brown to black UO2 flaky single crystal is obtained.

[0101] Comparing Examples 1, 5, and 6, the proportions of CsCl and CsF in the eutectic salt flux were changed, with the molar ratios of CsF being 45%, 50%, and 55%, respectively, and the resulting UO2 single crystals were not significantly different.

[0102] Example 7

[0103] (1) Preparation of reactant U3O8 powder

[0104] 1. Weigh 2.0g of UO2(NO3)2·6H2O and place it in an Al2O3 crucible. Under air atmosphere, place it in a muffle furnace at 750℃ and react for 22h to oxidize and generate dark green to black U3O8 powder.

[0105] 2. The phase purity of the U3O8 generated by the reaction was confirmed by powder diffraction (PXRD). The diffraction peak positions basically met the standard peak values ​​and there were no impurity peaks, confirming the phase purity of the U3O8 generated by the reaction. No further high-temperature treatment was required, and it was put into use for future reference.

[0106] (2) Growth of UO2 single crystals

[0107] 1. In a glove box filled with Ar gas, weigh 0.25g of U3O8 powder obtained in step (1) and put it into an Ag crucible;

[0108] 2. Weigh 6.3g of CsCl-CsF eutectic salt (where the molar ratio of CsF is 42%), mix and grind thoroughly, and then place the mixed eutectic salt and U3O8 powder in an Ag crucible;

[0109] 3. Cover the Ag crucible with the silver lid, and then place the Ag crucible inside the Al2O3 crucible;

[0110] 4. The mixture was heated from 25°C to 850°C at a heating rate of 350°C / h, and the temperature was maintained at 850°C for 26 hours.

[0111] 5. Then, the temperature is reduced to 380℃ at a rate of 4℃ / h, and the temperature control program is stopped. The temperature is allowed to cool naturally to room temperature. After further cleaning, a dark reddish-brown to black UO2 flaky single crystal is obtained.

[0112] Example 9

[0113] (1) Preparation of reactant U3O8 powder

[0114] 1. Weigh 2.0g of UO2(NO3)2·6H2O and place it in an Al2O3 crucible. Under air atmosphere, place it in a muffle furnace at 720℃ and react for 26h to oxidize and generate dark green to black U3O8 powder.

[0115] 2. The phase purity of the U3O8 generated by the reaction was confirmed by powder diffraction (PXRD). The diffraction peak positions basically met the standard peak values ​​and there were no impurity peaks, confirming the phase purity of the U3O8 generated by the reaction. No further high-temperature treatment was required, and it was put into use for future reference.

[0116] (2) Growth of UO2 single crystals

[0117] 1. In a glove box filled with Ar gas, weigh 0.3g of U3O8 powder obtained in step (1) and put it into an Ag crucible;

[0118] 2. Weigh 6.8g of CsCl-CsF eutectic salt (where the molar ratio of CsF is 40%), mix and grind thoroughly, and then place the mixed eutectic salt and U3O8 powder in an Ag crucible;

[0119] 3. Cover the Ag crucible with the silver lid, and then place the Ag crucible inside the Al2O3 crucible;

[0120] 4. The mixture was heated from 25°C to 880°C at a heating rate of 250°C / h, and the temperature was maintained at 880°C for 22h.

[0121] 5. Then, the temperature is reduced to 420℃ at a rate of 5℃ / h, and the temperature control program is stopped. The temperature is allowed to cool naturally to room temperature. After further cleaning, a dark reddish-brown to black UO2 flaky single crystal is obtained.

[0122] Comparative Example 1

[0123] (1) Preparation of reactant U3O8 powder

[0124] The method for preparing U3O8 powder is the same as in Example 1.

[0125] (2) Growth of UO2 single crystals

[0126] 1. In a glove box filled with Ar gas, weigh 0.1052g of U3O8 powder obtained in step (1) and put it into an Ag crucible;

[0127] 2. Cover the Ag crucible with the silver lid, and then place the Ag crucible inside the Al2O3 crucible;

[0128] 3. The mixture was heated from 25°C to 900°C at a heating rate of 300°C / h, and the temperature was maintained at 900°C for 24 hours.

[0129] 4. Then, the temperature was lowered to 400℃ at a rate of 3℃ / h, at which point the programmed temperature control was stopped, and the mixture was allowed to cool naturally to room temperature. After further cleaning, a dark brown to black uranium dioxide powder was obtained. A stereomicroscope photograph of the powder is attached. Figure 3-5 .

[0130] Comparing Example 1 and Comparative Example 1, it can be seen that U3O8 powder without flux can only be obtained as UO2 powder after high-temperature heat treatment.

[0131] Comparative Example 2

[0132] (1) Preparation of reactant U3O8 powder

[0133] The method for preparing U3O8 powder is the same as in Example 1.

[0134] (2) Growth of UO2 single crystals

[0135] 1. In a glove box filled with Ar gas, weigh 0.1052g of U3O8 powder obtained in step (1) and put it into an Al2O3 crucible;

[0136] 2. Weigh 3.1g of CsCl-CsF eutectic salt (where the molar ratio of CsF is 45%), mix and grind thoroughly, and then place the mixed eutectic salt and U3O8 powder in an Al2O3 crucible;

[0137] 3. The mixture was heated from 25°C to 900°C at a heating rate of 300°C / h, and the temperature was maintained at 900°C for 24 hours.

[0138] 4. Then, the temperature is reduced to 400℃ at a rate of 3℃ / h, and the temperature control program is stopped. The mixture is allowed to cool naturally to room temperature. After further cleaning, a dark green to black U3O8 powder is obtained.

[0139] Comparing Example 1 and Comparative Example 2, it can be seen that in the reaction without the use of a silver crucible, the U3O8 powder cannot be reduced to UO2 after high-temperature heat treatment due to the lack of a reducing agent.

[0140] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.

[0141] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.

[0142] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.

Claims

1. A method for preparing uranium dioxide single crystals using a eutectic salt flux, characterized in that, Includes the following steps: S1. Place U3O8 powder and CsCl-CsF eutectic salt into an Ag crucible; S2. Then, the Ag crucible is placed in a ceramic crucible and heat-treated in an inert atmosphere, followed by cooling to room temperature and cleaning to obtain UO2 single crystals. The preparation method of the U3O8 powder includes the following steps: S1a. One or more of uranyl tricarbonate, uranyl nitrate, and ammonium diuranate are placed in a ceramic crucible and reacted in a muffle furnace under an air atmosphere to obtain U3O8 powder. S1b. Detect the phase purity of the U3O8 powder prepared above. If U3O8 is not a pure phase, put the U3O8 powder into a ceramic crucible again, and react it in a muffle furnace under an air atmosphere. Repeat the above steps until the obtained U3O8 powder is a pure phase. S1c, Place the pure phase U3O8 powder into a ceramic crucible again and react it in a muffle furnace under an air atmosphere; S1d, then repeat step S1c 0~3 times; The cooling process in step S2 includes: cooling down to 300-500°C at a rate of 2-8°C / h, then stopping temperature control and allowing it to cool naturally to room temperature.

2. The method for preparing uranium dioxide single crystals using a eutectic salt flux according to claim 1, characterized in that, The reaction temperature in the muffle furnace is 600~800℃, and the reaction time in the muffle furnace is 10~40h.

3. The method for preparing uranium dioxide single crystals using a eutectic salt flux according to claim 1, characterized in that Cs The mass ratio of Cl-CsF eutectic salt to U3O8 powder is 10~50:

1.

4. The method for preparing uranium dioxide single crystals using a eutectic salt flux according to claim 1, characterized in that, In the CsCl-CsF eutectic salt, the molar percentage of CsF is 35-60%.

5. The method for preparing uranium dioxide single crystals using a eutectic salt flux according to claim 1, characterized in that, The heat treatment temperature in step S2 is 800~950℃, and the heat treatment time is 15~30h.

6. The method for preparing uranium dioxide single crystals using a eutectic salt flux according to claim 5, characterized in that, Heat to the heat treatment temperature at a rate of 200~400℃ / h.

7. A UO2 single crystal, characterized in that, It is prepared by the method for preparing uranium dioxide single crystal using eutectic salt flux as described in claim 1. The UO2 single crystal has a crystal size of (0.10~0.30) mm × (0.02~0.20) mm × (0.01~0.05) mm and a crystal morphology of plate-like or blocky single crystal.